Potensi Budaya Kemaritiman di Wilayah Raja Ampat - Zubair Mas'ud (Balai Arkeologi Provinsi Sulawesi Utara, 2020)
Raja Ampat is known as an archipelago located in West Papua and occupies the bird's head region of Papua. This study aims to explore the potential of maritime culture in the Raja Ampat region. The research method used was conducting surveys and extracting information from the local community. The data obtained is then described and interpreted to acquire an overview of various maritime relics based on cultural materials and their environment. The findings obtained are in the form of rock images of boats, traditional boats, docks, and villages. Based on research supporting the culture of living around the coast, the water environment reflects traces of maritime cultural activities. The utilization of the environment supports activities in the community's daily life.